Population and Civil Registration Service of Bandar Lampung City’s Digital Bureaucratic System in Realizing an Effective and Efficient Government - Sondika Ragani; Adrian E. Rompis; Santi Hapsari Dewi Adikancana (Fakultas Hukum Universitas Lampung, 2021)
Nowadays, technological developments cannot be avoided. Technological developments in this era are to facilitate every human activity. The development of technology today is marked by the number of applications that can facilitate the community's affairs. An example is the application of the Community Online Service from the Population and Civil Registry Office of Bandar Lampung City called Pelayanan Online Masyarakat Duduk Manis (Permen Manis). This application is expected to help community services to help manage population documents and realize an effective and efficient government. The problem identified is the application of digital bureaucracy in the Population and Civil Registration Office, or Dinas Kependudukan dan Pencatatan Sipil (Disdukcapil) of Bandar Lampung City realizes an effective and efficient government? The research uses normative legal research by collecting and analyzing secondary data. by looking to the public's comments, especially on Permen Manis application users in Bandar Lampung’s Civil Registry Office. By this article the researcher hope the government in Bandar Lampung could improve the services towards the people in Bandar Lampung.